Transformational Leadership and Job Satisfaction: Assessing the Influence of Organizational Contextual Factors and Individual Characteristics - Abelha, Daniel Martins (2018)
Purpose – In this study we investigate the influence of organizational contextual factors and individual characteristics on the relationship between transformational leadership and job satisfaction. Design/methodology/approach – Quantitative research, with data collected through electronic questionnaires, answered by 166 individuals from different types of organizations, areas of professional training, and gender, subsequently applying sequential regression analyses. Findings – The results indicate that the relationship between transformational leadership and job satisfaction is moderated by the followers’ gender, being stronger for female followers. The relationship is not affected by the followers’ area of professional training, nor by type of organization (public/private). The study also evidenced the importance of taking into account individual affective states in studies of work attitudes. Originality/value – The research examines boundary conditions for the effect of transformational leaders in modern organizations, expanding the knowledge on organizational contextual factors that strengthen their influence on employee attitudes, while also controlling for individual differences.